Perencanaan dan Pengembangan Sistem Pendidikan - Fatmawati H.A. Zakariah; Uun Hasunah; Agus Tinus (J-SES : Journal of Science, Education and Studies, 2026)
This study aims to examine the planning and development of Indonesia’s education system by focusing on four key pillars: strategic planning, educational needs assessment, quality and relevance planning, as well as efficiency and equity in education. A qualitative approach was employed using a systematic literature review design, drawing on academic publications and policy documents published between 2021 and 2025. Data analysis was conducted through thematic content analysis. The findings indicate that educational strategic planning has shifted toward more participatory and data-oriented practices, although limitations in human resource capacity remain a challenge. Educational needs assessment serves as a crucial foundation for designing targeted programs, particularly in addressing disparities in literacy, numeracy, and teacher distribution. Furthermore, quality and relevance planning emphasize the development of 21st-century competencies and alignment with labor market demands through adaptive curriculum policies. Meanwhile, issues of efficiency and equity continue to pose challenges, especially in terms of resource allocation and access to education in disadvantaged regions. Therefore, the integration of these four pillars is essential to achieving a high-quality, inclusive, and sustainable education system